A room-temperature, low-impedance and high-IF-bandwidth terahertz heterodyne detector based on bowtie-antenna-coupled AlGaN/GaN HEMT. (1st February 2023) - Ding, Qingfeng; Zhu, Yifan; Xiang, Lanyong; Zhang, Jinfeng; Li, Xinxing; Jin, Lin; Shangguan, Yang; Sun, Jiandong; Qin, Hua
Abstract: In this paper, a 330 GHz terahertz heterodyne detector based on bowtie-antenna-coupled AlGaN/GaN high-electron-mobility transistor (HEMT) is designed and demonstrated. The bowtie antenna and a silicon lens couple the terahertz wave into a transmission line, in which the HEMT's channel generates both self-mixing and heterodyne signals. Compared to field-effect detectors without front low-noise amplifiers and output impedance matching, this detector boosts the intermediate-frequency (IF) bandwidth to 2.9 GHz due to a low output impedance of 505 Ω while maintaining a comparable sensitivity. With further sensitivity enhancement, such detectors would be developed into room-temperature, high-sensitivity, and high-IF-bandwidth heterodyne arrays.